The Prospect and Challenges of Repurposing Established Drugs in Pulmonary Arterial Hypertension - Sila Ozlem Sener; Rateep Nasim; Talat Nasim (MDPI AG, 2024)
Pulmonary arterial hypertension (PAH) is a progressive disorder caused by the narrowing of small blood vessels in the lungs, which, in the absence of therapies, leads to right heart failure and premature death. No cure for this devastating disorder is known. Current management therapies aim to improve symptoms, and hence, there is a need to identify novel therapeutic interventions. The major objectives of this review are to critically evaluate current treatment strategies and highlight the challenges and prospects of established drugs and natural products for the resolution of PAH.